PREGNANCY DIAGNOSIS IN GOATS BY USING TWO DIFFERENT ULTRASOUND PROBES - R. I. A. Raja-Khalif; M. M. Rahman; W. E. Wan-Khadijah; R. B. Abdullah (Journal of Animal and Plant Sciences, 2014)
Information on pregnancy detection in goats using real-time ultrasonography is still lacking compared with that in sheep. Ultrasound scanner with transrectal and transabdominal probes was used to observe and identify foetal related structures and images during pregnancy of does. Does were synchronized for estrus and naturally served or artificially inseminated to obtain pregnancy and subsequently scanned using both probes. Observation and identification of sac, non-echogenic area and foetus-foetal heart-uterine wall-amniotic fluid were detected from days 21 to 49 of gestation. Other structures such as placentomes-foetus-foetal heart-spinal cord-ribs-foetal organ (absence and presence) were easily detected during middle stage of gestation (days 51 to 119 of gestation). During third trimester (days 120 to 143 of gestation), only detection of placentomes was observed. Overall accuracy on prediction of each stage of gestation for first, second and third stages of gestation using transrectal and transabdominal probes were 96, 99 and 100%, respectively. In conclusion, early detection of pregnancy is promising with transrectal probe from days 21 to 50 of gestation. Transabdominal probe is practical from days 51 to 145 of gestation. Both probes are needed to detect pregnancy in does since their effectiveness is mutually exclusive for the different stages of gestation.
Keywords: Goats; Ultrasonography; Transrectal; Transabdominal; Foetal structures